The People Trafficking Princes: Slaves, Silver and State Formation in Poland. (2nd July 2020) - Roach, Andrew
ABSTRACT: The Piast princes were traders in slaves which was the foundation of their power. Conversion to Christianity was part of a wider project at stabilisation which can be compared to Coase's 'firm', whereby previously 'ad hoc' market arrangements between agents are formalised in return for regular remuneration. This proved timely as the establishment of the Piast state coincided with a decline of the trade with the east, but enabled the Piasts to take a larger share of what commerce remained. Despite their best efforts, in the 1030s the Piasts succumbed to internal pressures and powerful neighbours. Nevertheless, the structures they created provided the basis for the kingdom of Poland.